THE INFLUENCE OF ADVERTISING AND BRAND REPUTATION ON BRAND IMAGE AND ITS IMPLICATIONS ON HANBODY MARINA PURCHASE DECISIONS (AT THE NUSANTARA SHOP, TEBING TINGGI) - Indriani Nainggolan; Putri Ramadhani; Fitrianingsih; Imelda Mardayanti (RADJA PUBLIKA, 2025)
This study analyzes the influence of advertising and brand reputation on brand image and its implications on Hanbody Marina purchasing decisions. (at the Nusantara Tebing Tinggi store). Using a quantitative method with a sample of 96 respondents using the Cochran formula, data were collected through questionnaires and analyzed with SMART PLS 3.0. The results showed that advertising had a significant effect on the brand image of Marina handbody products at the Nusantara Tebing Tinggi Store. Brand reputation has a significant influence on the brand image of Marina handbody products at Toko Nusantara Tebing Tinggi. Advertisements do not influence the purchasing decision for Marina handbody products at the Nusantara Tebing Tinggi Store. Brand reputation has a significant influence on purchasing decisions for Marina handbody products at Toko Nusantara Tebing Tinggi. Brand image has a significant influence on purchasing decisions for Marina handbody products at the Nusantara Tebing Tinggi Store. Advertisement influences the purchasing decision of Marina handbody products through brand image as an intervening variable at Toko Nusantara Tebing Tinggi. Brand reputation influences the purchasing decision of Marina handbody products through brand image as an intervening variable at Toko Nusantara Tebing Tinggi.